Disrupting narrow conceptions of justice: Exploring and expanding 'bullying' and 'upstanding' in a university honors course. (November 2020) - Farley, Jennifer; Gallagher, Jennifer; Richardson Bruna, Katherine
The term 'upstanding' encompasses actions and behaviors grounded in one's defense of their own beliefs and others. While such broad application of the term has merit, from a critical education perspective it lacks direction. To efficaciously address injustice, upstanding action must go beyond one's beliefs. A directional application of upstanding behavior, or the notion of 'upstanding for justice, ' frames upstanding as action to address chronic social victimization via systems of oppression. In this article, we describe the development of a new heuristic to support students' understanding of upstanding and detail the university honors course in which we used the heuristic to explore the phenomena of 'bullying' and historical injustice to expand ideas of 'upstanding'. Results indicate that students in the course broadened their conceptions of justice and the use of historical cases aided in their understanding of the interplay between individual agency and social structure in social justice efforts.